2004
DOI: 10.1109/tmag.2004.830165
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Media Fabricated by Lithography and Argon-Ion Milling

Abstract: Using continuous film prepared by lower gas sputtering, a dot array with a more stable single domain was achieved. The requirements for magnetic properties of patterned media were different from that of perpendicular continuous-film media. The switching field distribution in dot arrays depends on fluctuation in dot size. The smallest size of dot arrays, fabricated by most simple method as lithography and ion-milling, is 50 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…INTRODUCTION THE origin and control of the distribution of the switching fields (SFD) of nanostructured arrays of single-domain, perpendicularly-oriented magnetic materials is mystery in need of a solution before data storage schemes based on bit patterned arrays and digital logic devices based on magnetic cellular automata can be successfully implemented [1][2][3][4][5][6]. Several causes have been proposed, lithographic [3], microstructural [4], and magnetic [5].…”
Section: Sponsoring/monitoring Agency Name(s) and Address(es) 10 Spomentioning
confidence: 99%
See 1 more Smart Citation
“…INTRODUCTION THE origin and control of the distribution of the switching fields (SFD) of nanostructured arrays of single-domain, perpendicularly-oriented magnetic materials is mystery in need of a solution before data storage schemes based on bit patterned arrays and digital logic devices based on magnetic cellular automata can be successfully implemented [1][2][3][4][5][6]. Several causes have been proposed, lithographic [3], microstructural [4], and magnetic [5].…”
Section: Sponsoring/monitoring Agency Name(s) and Address(es) 10 Spomentioning
confidence: 99%
“…Several causes have been proposed, lithographic [3], microstructural [4], and magnetic [5]. Indeed, these are not mutually exclusive, as the orientation of the grains affects their anisotropy, providing ideal sites for nucleation embryos [6].…”
Section: Sponsoring/monitoring Agency Name(s) and Address(es) 10 Spomentioning
confidence: 99%
“…Even carefully prepared samples of thin magnetic films on non-magnetic surfaces and magnetic islands patterned from such films have been found to have a wide distribution of nucleation volumes [10][11][12]. For example, experiments on Co/Pd islands as large as 5 µm [12] have shown that the switching field distribution (SFD) of patterned islands is a reflection of the spatial variation of the nucleation volume of the continuous film from which the islands were formed.…”
Section: Introductionmentioning
confidence: 99%
“…Two major fabrication methods exist for BPM (Thomson et al 2006;Shaw et al 2007;Kitade et al 2004). In the first method, a layer of high coercivity magnetic material is first deposited on a flat substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, a main disadvantage of this method is that the magnetic material can easily be damaged by the ion etching patterning process. Furthermore, material removed during ion-etching can be re-deposited on the media during the patterning process, which is undesirable (Shaw et al 2007;Kitade et al 2004). In the second method, the substrate is lithographically prepatterned into islands, or so-called pillars, before the magnetic material is deposited.…”
Section: Introductionmentioning
confidence: 99%